Praia de Ponta Negra: uma abordagem da paisagem costeira de 1970 a 2010, Natal/RN - Maciel, Ana Beatriz Câmara (2011)
With process urbanization process the Brazilian cities have been goin through, Natal/RN does not differ from the other ones, it has had a fast, inordinate and planned urbanization, but not applied, it has caused a high increase of social environmental problems. One of the worrying problems observed is the change in the coastal landscape, which has caused serious damage to the city‟s population, more specifically, of Ponta Negra beach neighborhood. For the geographical studies, the issue, concerning the occupation of the beaches that has been getting higher and higher in the last decades is extremely important because these, in addition to being used as homes in the new urban configuration, have incorporated new ways of environmental interference, without a simultaneous advance of knowledge which would be necessary for a more suitable and rational use of litoral spaces. Thus, the current assignment aimed to focus the coastal landscape of Ponta Negra Beach, in the city of Natal/RN, checking and analyzing the effects caused by anthropic and natural action, and the way it reflects in the quality of life of the resident, working population and of the frequenters as well as the landscape transformations in the area which is object of study, from 1970 through 2010. The methodology used followed to stages, the first concerned the theoretical work bibliographic surveying and composition; and second one the empirical work marking of the environmental characterization and application of the questionnaires. So, we can measure that Ponta Negra, is very susceptible to environmental changes, the ones caused by the natural dynamics of the beach, as well as the human actions (society) in this really fragile and mutable space, so it needs, a more profound systematic study about the coastal landscape. In order to reach a minimization of the change of the landscapes in the coastal zones there must be an integrated management of the environments, based on the planning of actions and territorial reordination of the occupations of these so important spaces, environmentally, as well as socioeconomically. Whereas, only this way, we will have a sustentable development and a suitable use of that space